The body and medicine - Wieczorkowska, Magdalena (Body and society. Sociology of the body in research and theoretical concepts, 2023)
The aim of this chapter is to demonstrate how medical knowledge influences the perception of the body, its meaning and its transformations. The presented theories are discussed in chronological order: first, the humours theory; next, the medieval model, which involves treating disease as a punishment for sins and enforcing body regimes; and then, modern medicine and the biomedical model of health and disease. The contemporary processes that place the body in medical shackles conclude in the medicalisation processes, which continue to spread to an increasing number of areas connected to human life and body, making it a subject of medical intervention and control. Other theories are concerned with curative medicine, preventive medicine, and medicine aiming at fulfilling wishes, as well as their influence on the social construction of the body. There is also a comparison of the assumptions underlying modern medicine and alternative medicine in the context of the perception and treatment of the human body. The relationship between the body and medicine does not end with one’s death as a human may become an organ donor after his or her death or may leave instructions regarding the use of his or her body after death. The achievements of medicine also modify the near-future perception of the body, posing questions about the limits of interventions, boundaries between fixing the body and improving the body, and, thus, the limits of humanity itself. This is the focal point of the final discussed theory, which introduces the context of cyborgisation. The second part of the chapter offers selected key notions and their synthetic description. The third part of the chapter presents a concise description of studies on medicalisation, geneticisation, donation, and transplantation.